DOAK DINDIN - Cut Mutia; Wimbrayardi Wimbrayardi; Jagar Lumbantaoruan (FBS Universitas Negeri Padang, 2018)
Abstract Eliciting and giving appreciation to society especially among the students toward traditional music, the lack of insight of educators in educational institutions makes students less knowledge about their traditional culture. The artist was interested in working a music project that based on talempong pacik learning in non public school art into the form of music school composition. The school of music is a music that is played by the students together in school and contains the education values. If it is seen from the level of difficulty, the artist provided material to be played which was match to the ability possessed by students of the school. It encouraged the artist to explore Cak Dindin song, working on rhythm and melody in talempong pacikgua cak dindin into an art work form of creative music composition entitle Doak Dindin inspired by one of the repertoires of talempong pacik born in Minangkabau into some elements and techniques of farming out music that exists on the theory of Western music like unisono, interloking, proposta, riposta, singkopasi as well as using major and minor tones and the presence of diminusi and augmentation of the tone. This art work was played by the 8 players of musical instruments, namely talempong dasar, talempong paningkah, talempong anak, talempong rea, gandang tambua, sarunai, guitar, rapa'i and cymbals. Keywords: talempong, schools, cultural arts, composition